What happens next? A 2‐year follow‐up study into the outcomes and experiences of an adapted Dialectical Behaviour Therapy skills training group for people with intellectual disabilities. (9th April 2019) - Hewitt, Olivia; Atkinson‐Jones, Katherine; Gregory, Hannah; Hollyman, Jonathan
Accessible summary: Dialectical Behaviour Therapy (DBT) is a therapy to help people manage their feelings. We ran a DBT group for people with an intellectual disability. The group seemed to help people feel better and manage their feelings, even after the group ended. The group was 2 years ago. We talked to three people who went to the group to see what people still remembered from the group and if DBT was still helping them. We think having a top‐up session might help people to remember and practise ideas from the group. Abstract: Background: This paper reports quantitative and qualitative follow‐up data from three participants who attended a Dialectical Behaviour Therapy (DBT) group for people with an intellectual disability. Materials and Methods: Quantitative data regarding psychological well‐being, psychological distress (measured using the Psychological Therapies Outcome Scales; PTOS) and quality of life (measured using the Health of the Nation Outcome Scales—Learning Disability; HONOS‐LD) are reported for pre‐group, post‐group and at 6‐month and 2‐year follow‐up. Interviews were conducted with participants post‐group and at 2‐year follow‐up. Data were analysed using thematic analysis. Results: Improvements in scores on measures of psychological well‐being, psychological distress and quality of life appear to be maintained at 6‐month follow‐up, but scores at 2‐year follow‐up suggest a return to baseline. Qualitative self‐report data suggest a number of interesting ways participants adapted and individualised techniques from the group, as well as suggesting possible barriers to maintaining change in the longer term. Conclusions: Clinical implications are considered to improve effectiveness of similar interventions, as well research implications in order to improve knowledge about the longer term impact of group DBT interventions.